2019
DOI: 10.1002/ijc.32775
|View full text |Cite
|
Sign up to set email alerts
|

High‐risk Stage III colon cancer patients identified by a novel five‐gene mutational signature are characterized by upregulation of IL‐23A and gut bacterial translocation of the tumor microenvironment

Abstract: The heterogeneities of colorectal cancer (CRC) lead to staging inadequately of patients' prognosis. Here, we performed a prognostic analysis based on the tumor mutational profile and explored the characteristics of the high-risk tumors. We sequenced 338 colorectal carcinomas as the training dataset, constructed a novel five-gene (SMAD4, MUC16, COL6A3, FLG and LRP1B) prognostic signature, and validated it in an independent dataset from The Cancer Genome Atlas (TCGA). Kaplan-Meier and Cox regression analyses con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 41 publications
4
33
1
Order By: Relevance
“…Some of the tumour genera of (possible) oral origin identi ed in our study, were associated with tumour mucosa previously, namely Fusobacterium, Campylobacter, Leptotrichia, Parvimonas, Gemella, Granulicatella, Eikenella, Selenomonas, Neisseria, Streptococcus, Alloprevotella, Veilonella, Haemophilus [8,31,32,[61][62][63][64][65][66][67][68]. In contrast, Solobacterium was reported increased [31], while Slackia and Pseudomonas were shown to be decreased [12,19] in fecal samples of CRC patients compared to healthy donors, and, in one epidemiological study, the presence of Treponema in the oral cavity was associated with increased risk of CRC [29], but none of these were previously associated with tumour mucosa.…”
Section: Tumour Crc Microbial Subtypessupporting
confidence: 57%
“…Some of the tumour genera of (possible) oral origin identi ed in our study, were associated with tumour mucosa previously, namely Fusobacterium, Campylobacter, Leptotrichia, Parvimonas, Gemella, Granulicatella, Eikenella, Selenomonas, Neisseria, Streptococcus, Alloprevotella, Veilonella, Haemophilus [8,31,32,[61][62][63][64][65][66][67][68]. In contrast, Solobacterium was reported increased [31], while Slackia and Pseudomonas were shown to be decreased [12,19] in fecal samples of CRC patients compared to healthy donors, and, in one epidemiological study, the presence of Treponema in the oral cavity was associated with increased risk of CRC [29], but none of these were previously associated with tumour mucosa.…”
Section: Tumour Crc Microbial Subtypessupporting
confidence: 57%
“…Moreover, P. micra may contribute to the pathogenesis of periodontitis by stimulating Toll-like receptor 4, nucleotide binding oligomerization domain containing (NOD)1 and NOD2 (54). It has also been reported that P. micra may be involved in gut bacterial translocation and the upregulation of interleukins in the tumor microenvironment (55). A previous study demonstrated that APC Min/+ mice gavaged with P. micra exhibited a significantly higher tumor burden and tumor load, and cell proliferation was significantly higher in the colon tissues of P. micra gavaged germ-free mice compared with control mice (56).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the integrated analysis of 16s rRNA and metabolomics data showed that there were 19 functional relationship pairs, including eight altered microbiota (e.g., Ruminiclostridium and Prevotellaceae_UCG_001) and 16 disturbed metabolites (e.g., C10H11NO3 and C21H32O8) between the JK5G and model groups. Actually, Alloprevotella has been regarded as the cancer-related bacteria in colon cancer or visceral leishmaniasis (30,31). Moreover, a previous study showed that the abundance of the Ruminiclostridium genus was related to the enhancement of animal immune responses to spore adsorbent antigen and probiotics (32).…”
Section: Discussionmentioning
confidence: 99%